SEJARAH PERKEMBANGAN USAHA KERAJINAN RUMAH TENUN PUCUK REBUNG KAMPUNG BANDAR SENAPELAN KOTA PEKANBARU TAHUN 2012-2019 - Santri Hanifa Zahra; Isjoni Isjoni; Bedriati Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The shoot of shoots tenun house is a house located on the commercial street of Senapelan bandar village, Pekanbaru city. This house is a house inhabited by the women of the KSM (Self-Help Group) of the Bandar village who have been keeping traditional woven fabrics in their safekeeping since 2012. This program received help from PNPM (Community Empowerment National Program) in the form of weaving instructors and tools and materials. This weaving mill is chaired by Mrs. Wawa Edini as the janitor of the weaving mill, who is assisted by other members of the weaving mill and currently this weaving mill is managed by BI (Bank Indonesia). to learn more about the development of Pucuk Rebung Weaving House handicraft business in Bandar Senapelan Village, Pekanbaru City in 2012-2019. The data analysis used qualitative research methods consisting of several stages, namely data collection, data reduction, data presentation, and conclusion. As a result of this research, this weaving mill is a house that preserves traditional Malaysian weaves since 2012, in its development, this house has gone through quite rapid development from tools for weaving to kinds of woven handicraft production. This weaving house is known to the wider community in the conservation of traditional woven fabrics to various other Asian countries such as France, Singapore, Malaysia.Key Words: History, Development, Weaving House, Village Bandar, Senapelan